(untitled) (Salam International Academic Journal, 2025)
The rapid adoption of remote work has transformed contemporary work arrangements, presenting both opportunities and challenges for employee well-being, particularly in developing and fragile contexts. This study examines the impact of remote work on employee well-being and investigates the mediating role of perceived organizational support (POS) among employees of local non-governmental organizations (NGOs) in Kabul, Afghanistan. Grounded in organizational support theory and well-being literature, the study adopts a positivist research philosophy and employs a quantitative research design. Data were collected through a structured questionnaire from a sample of 282 NGO employees engaged in remote or hybrid work arrangements. Statistical analyses were conducted to test the direct relationship between remote work and employee well-being, as well as the mediating effect of perceived organizational support. The findings reveal that remote work has a significant influence on employee well-being, encompassing physical, mental, and emotional dimensions. Moreover, perceived organizational support was found to play a crucial mediating role, mitigating the negative effects of remote work-related stress, isolation, and work–life boundary blurring. The results highlight that employees who perceive higher levels of organizational support such as access to mental health resources, effective communication, and supportive policies report better overall well-being. This study contributes to the limited empirical literature on remote work in the Afghan NGO sector and underscores the importance of strengthening organizational support mechanisms to enhance employee well-being in remote work settings. Practical implications for NGO management and policymakers are discussed.